Adaptive Immune Responses in Primary Cutaneous Sarcoidosis - Matteo Bordignon; Paola Rottoli; Carlo Agostini; Mauro Alaibac (Clinical and Developmental Immunology)
Sarcoidosis is a multisystemic inflammatory disorder with cutaneous lesions present in about one-quarter of the patients. Cutaneous lesions have been classified as specific and nonspecific, depending on the presence of nonnecrotizing epithelial cell granulomas on histologic studies. The development and progression of specific cutaneous sarcoidosis involves a complex interaction between cells of the adaptive immune systems, notably T-lymphocytes and dendritic cells. In this paper, we will discuss the role of T-cells and skin dendritic cells in the development of primary cutaneous sarcoidosis and comment on the potential antigenic stimuli that may account for the development of the immunological response. We will further explore the contributions of selected cytokines to the immunopathological process. The knowledge of the adaptive immunological mechanisms operative in cutaneous sarcoidosis may subsequently be useful for identifying prevention and treatment strategies of systemic sarcoidosis.